O problema de corte de estoque com uso e venda de retalhos: uma proposta de otimização para a sustentabilidade ambiental - Coelho, Karen Rocha [UNESP] (2015)
Considering the theories of Ecological Modernization and Cleaner Production (CP), this work relates the sustainability and the operational research through a variation of cutting stock problem with usable leftovers (CSPUL). In the CSPUL a set of standard objects (boutht from suppliers) or non-standard objects (retails generated in previous cutting processes), which area available in stock, must be cut in order to produce a set of demanded items with dimensions and specifed quantities. The objective consists of determining the best way to cut the objects optimizing an objective function and considering that a certain amount of retails can return to the stock to meet future demands. Differently of the work, the CSPUL will be solved, however, retails in stock in addition to being used, they can be sold of this option is more attractive. This problem is named of cutting stock problem with usable leftovers and sale retails (CSPULSR) and has the objective of maximizing the profit. To model the CSPULSR, was modified a mathematical model proposed in the literature and, to solve it, the simplex method with column generation was used. As the obtained solution to this problem is not integer, were proposed two heuristic procedures that also consider the usable leftovers. Computational tests were performed with randomly generated instances considering static problems and a simulation by periods of time, in which retails generated in a period stay available for use and/or sale of the next period. With these tests, very good performance of the proposed strategy was verified. Due to the particularities of this strategy, also was realized an analysis and discussed the results considering implications for CP, which is a strategy that intends to integrate environmental objective into industrial processes, in order to reduce the amount of waste and emissions. It also aligns the theory of Ecological Modernization as it seeks to reduce the environmental...